Tribute to Justice Ruth Bader Ginsburg - Mokgoro, Yvonne (Columbia Journal of Gender and Law, 2013)
It is indeed a great pleasure to pay a special tribute to a global trailblazer who has had a profound impact on the legal thinking of many scholars and jurists around the world- men and women alike. The visit of Justice Ginsburg to the Constitutional Court of South Africa in 2006, when she delivered her speech entitled “The Value of a Comparative Perspective in Constitutional Adjudication,” will always be fondly remembered. It was quite refreshing and indeed many at the time marvelled at a United States Supreme Court Justice advocating the use of comparative law to enhance the quality of constitutional adjudication globally. In that speech, she cited with admiration Section 39 of the Constitution of South Africa, which enjoins the judiciary to apply international law and foreign law, and provides that: “When interpreting the Bill of Rights, a court must consider international law; and may consider foreign law.” Justice Ginsburg noted that other modem constitutions such as that of Spain and India have similar provisions. The importance of the comparative perspective in the legal interpretive process has not escaped Justice Ginsburg and it is in that regard too that we honour her. The incredible journey which she has travelled has not just been American or South African, nor have her battles for women’s equal rights been confined to certain territories. They have been global. It is that oneness in her advocacy that should be cherished and saluted.